Hepatic IRF3 fuels dysglycemia in obesity through direct regulation of Ppp2r1b - Patel, Suraj J.; Liu, Nan; Piaker, Sam; Gulko, Anton; Andrade, Maynara L.; Heyward, Frankie D.; Sermersheim, Tyler; Edinger, Nufar; Srinivasan, Harini; Emont, Margo P.; Westcott, Gregory P.; Luther, Jay; et al. (Science translational medicine, 2022)
Inflammation has profound but poorly understood effects on metabolism, especially in the context of obesity and nonalcoholic fatty liver disease (NAFLD). Here, we report that hepatic interferon regulatory factor 3 (IRF3) is a direct transcriptional regulator of glucose homeostasis through induction of Ppp2r1b, a component of serine/threonine phosphatase PP2A, and subsequent suppression of glucose production. Global ablation of IRF3 in mice on a high-fat diet protected against both steatosis and dysglycemia, whereas hepatocyte-specific loss of IRF3 affects only dysglycemia. Integration of the IRF3-dependent transcriptome and cistrome in mouse hepatocytes identifies Ppp2r1b as a direct IRF3 target responsible for mediating its metabolic actions on glucose homeostasis. IRF3-mediated induction of Ppp2r1b amplified PP2A activity, with subsequent dephosphorylation of AMPK. and AKT. Furthermore, suppression of hepatic Irf3 expression with antisense oligonucleotides reversed obesity-induced insulin resistance and restored glucose homeostasis in obese mice. Obese humans with NAFLD displayed enhanced activation of liver IRF3, with reversion after bariatric surgery. Hepatic PPP2R1B expression correlated with HgbA1C and was elevated in obese humans with impaired fasting glucose. We therefore identify the hepatic IRF3-PPP2R1B axis as a causal link between obesity-induced inflammation and dysglycemia and suggest an approach for limiting the metabolic dysfunction accompanying obesity-associated NAFLD.